2012
DOI: 10.1371/journal.pone.0046585
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue as a Cerebral Metabolic and Hemodynamic Enhancer

Abstract: By restoring mitochondrial function, methylene blue (MB) is an effective neuroprotectant in many neurological disorders (e.g., Parkinson’s and Alzheimer’s diseases). MB has also been proposed as a brain metabolic enhancer because of its action on mitochondrial cytochrome c oxidase. We used in vitro and in vivo approaches to determine how MB affects brain metabolism and hemodynamics. For in vitro, we evaluated the effect of MB on brain mitochondrial function, oxygen consumption, and glucose uptake. For in vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 37 publications
3
64
10
Order By: Relevance
“…Whether this is sustained after chronic in vivo exposure remains to be studied. Indeed, that the drug has a powerful effect on mitochondrial function supports a possible neuroprotective and antioxidant action, as has been suggested for MB and other antioxidants in treating mood disorders (Lin et al, 2012). Both of these mechanisms are recognised as being central to depression and its treatment (Harvey, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Whether this is sustained after chronic in vivo exposure remains to be studied. Indeed, that the drug has a powerful effect on mitochondrial function supports a possible neuroprotective and antioxidant action, as has been suggested for MB and other antioxidants in treating mood disorders (Lin et al, 2012). Both of these mechanisms are recognised as being central to depression and its treatment (Harvey, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…MB enhances global glucose uptake, oxygen consumption, and CBF in normal rats. 12 In addition, MB markedly potentiates forelimb evoked blood oxygenation level-dependent (BOLD), CBF and cerebral metabolic rate of oxygen (CMRO 2 ) changes focally in the forelimb somatosensory cortices, 13 suggesting that MB has effects localized to regions with enhanced activity or metabolic stress. Moreover, during mild hypoxia, 13 MB-treated rats are better able to sustain global glucose uptake, oxygen consumption, and CBF than are vehicletreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MB can induce long-lasting effects by modifying mitochondrial pathways. 11 In vivo studies also show that MB significantly affects cerebral metabolism, hemodynamics, and evoked responses in normal rats; namely, that, MB enhances global glucose uptake, oxygen consumption, CBF 12 and evoked responses. 13 Recently, MB treatment has been shown to reduce behavioral impairments in animal models of Parkinson's disease 14 and Alzheimer's disease, 15,16 and to reduce cerebral infarct volume by histology.…”
Section: Introductionmentioning
confidence: 99%
“…54 Interestingly, MB had minimal effects on CBF, when compared to vehicle-treated animals. Previous studies have reported that MB does not affect CBF 55 or increased CBF 56 only slightly in normal animals. In this study, acute and delayed MB increased CBF values only on day 14, compared to vehicle-treated animals.…”
Section: Magnetic Resonance Imaging Characterization Of Traumatic Bramentioning
confidence: 64%